Análisis de la asignación del agua para el sector hidroeléctrico en colombia a partir de los discursos (2021)
This document analyzes water allocation based on the discourses of the hydroelectric sector in Colombia in the framework of water justice. It starts from a critical analysis of the discourse of the environmental impact studies of 22 hydroelectric plants, which due to their power generation capacity required an environmental license from the National Environmental Licensing Authority - (hereinafter ANLA), contrasted with academic literature and social expression to identify specific contexts in each project. Based on the concept of water justice and the discourses identified in the literature, the hydroelectric projects were characterized to construct the following categories of analysis: i) Limitations in recognition, ii) Legitimation and participation processes of the projects and iii) Prioritization in the water distribution. As a result, it was evidenced that there are no criteria of equity, efficiency and sustainability in water distribution and that the granting of environmental licenses for hydroelectric projects is not carried out under principles of water justice.